Investigation of the physical properties of Bi1.5-xCdxZn0.92Nb1.5O6.92-x/2 pyrochlore ceramics - (:unkn) unknown (SPRINGER, 2013)
For the purpose of dielectric parameters tuning Bi1.5Zn0.92Nb1.5O6.92 (BZN) pyrochlore ceramics were subject to cadmium doping in accordance to the chemical formula; Bi1.5-xCdxZn0.92Nb1.5O6.92-x/2 for 0.10 a parts per thousand currency sign x a parts per thousand currency sign 0.50. The main physical properties of the doped samples were investigated by means of X-ray diffraction, scanning electron microscopy associated with energy dispersion spectroscopy, temperature dependent dielectric constant and temperature dependent electrical resistivity to obtain the crystalline structure, the lattice parameter, the relative density, the surface morphology and chemical composition. Optimization of single phase Cd doped samples were possible for x a parts per thousand currency signaEuro parts per thousand 0.14, beyond this limit, ZnO and Zn3Nb2O8 minor phases grow through the structure of the BZN. For samples which exhibit single BZN phase, the dielectric constant, the electrical resistivity and the resistivity activation energy increased with increasing Cd content. The maximum obtainable dielectric constant as 259 and 224 with high signal quality factor of 690 and 1090 at 25 and 200 A degrees C, respectively, was for the sample doped with 0.14 Cd. These values are promising for implantation of BZN in RF and microwave technology as a resonator with high quality signal.
Keywords: Mixing; Composites; X-ray methods; Dielectric; Electrical properties; DOPED BI1.5ZN0.92NB1.5O6.92 PYROCHLORES; DIELECTRIC-PROPERTIES; CUBIC PYROCHLORE; THIN-FILMS